The role of midwives in preventing malaria in pregnant women: qualitative study from South-West Sumba Regency, Indonesia - Kencanawati, Dewa Ayu Putu Mariana; Ndapa, Conchita Emiliana; Martha, Evi (Intelektual Pustaka Media Utama, 2025)
Pregnant women in Indonesia, particularly in the Southwest Sumba Regency are faced with high malaria incidence. To overcome the challenge, midwives play a crucial role in integrating malaria services into maternal and child health (MCH) program. Therefore, this study aimed to examine the role of midwives in the implementation of integrated MCH services in the Southwest Sumba district. The location and participants were carefully selected and data collection was performed using the semi-structured interview method, which was divided into three sections. These included i) understanding of midwives regarding malaria and dangers to pregnant women, ii) the implementation of integrated malaria services for the MCH program, and iii) the role of midwives. The collected data were thematically analyzed and narratively presented based on the themes. The results showed that midwives in North Kodi District had a limited understanding of malaria. Consequently, the implementation of integrated MCH services, including specialized preventive education for pregnant women, was not at the optimal level. This phenomenon showed the need for malaria education, preparation of service standards, facilitative supervision, and cross-sectoral collaboration.